1995
DOI: 10.1007/bf01616741
|View full text |Cite
|
Sign up to set email alerts
|

“Helper:” A critical events prompter for unexpected emergencies

Abstract: These data demonstrate the value of a prompting device at the anesthesia workstation. We foresee the use of such prompters in many areas of medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Two of the remaining 3 studies showed no improvement in neonatal (Bould et al 40 ) and adult (Schneider et al 32 ) resuscitation. Two of the remaining 3 studies showed no improvement in neonatal (Bould et al 40 ) and adult (Schneider et al 32 ) resuscitation.…”
Section: Evaluation Of the Aidmentioning
confidence: 99%
See 3 more Smart Citations
“…Two of the remaining 3 studies showed no improvement in neonatal (Bould et al 40 ) and adult (Schneider et al 32 ) resuscitation. Two of the remaining 3 studies showed no improvement in neonatal (Bould et al 40 ) and adult (Schneider et al 32 ) resuscitation.…”
Section: Evaluation Of the Aidmentioning
confidence: 99%
“…The content of 13 cognitive aids was derived from existing national guidelines 18,19,26,29,30,[32][33][34][35][36][37]40,42 including all of the aids relating to management of cardiac arrest of adults [32][33][34][35][36][37] and neonates. 40 This may reflect the existence of established national and international guidelines for cardiopulmonary resuscitation.…”
Section: Content Of the Cognitive Aidmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulation studies of basic life support, 186 -190 advanced life support, 191,192 and anesthetic emergencies 193,194 demonstrated improved performance when checklists or cognitive aids were used. However, 1 simulation study demonstrated delayed completion of 2 cycles of CPR 195 when individuals not adept at cell phone operation used a cell phone-based cognitive aid.…”
Section: Improving Resuscitation Skills Checklists/cognitive Aidsmentioning
confidence: 99%